Further evaluation of a functional analysis of moderate‐to‐vigorous physical activity in young children. Issue 2 (25th April 2014) - Larson, Tracy A.; Normand, Matthew P.; Morley, Allison J.; Miller, Bryon G.
<x xml:space="preserve">Abstract</x> Inadequate physical activity increases the risks related to several health problems in children; however, increasing physical activity mitigates these risks. In this study, we examined the relations between moderate‐to‐vigorous physical activity (MVPA) and several environmental conditions (attention, interactive play, alone, escape) with 4 preschool children. We compared the experimental conditions to a control condition and a naturalistic baseline according to a combined multielement and reversal design. Results indicated that all participants were most active in the interactive play condition and that the percentage of MVPA varied across experimental and control conditions. In addition, the frequency and duration of bouts of MVPA were greatest in the interactive play condition. The current study presents a methodology for the identification of environmental contingencies that support increased levels of MVPA in young children, and it holds promise for improving our understanding of the variables related to physical activity.